Bioluminescence Analysis of Antibacterial Photodynamic Therapy Using Methylene Blue Mediated by Low-Intensity Level Laser Against Cariogenic Biofilms - Esteban Florez, Fernando Luis; Mendonca de Oliveira, Morgana Regina [UNESP]; Oliveira Junior, Osmir Batista de [UNESP]; Hiers, Rochelle Denise; Khajotia, Sharukh Soli; Pretel, Hermes [UNESP] (Mary Ann Liebert, Inc, 2018)
Objective: A non-destructive and real-time bioluminescence (BL) assay was used to determine the utility of antimicrobial photodynamic therapy (aPDT) treatments mediated by methylene blue (MB) and laser irradiation (LI) against intact biofilms that are capable of producing caries (cariogenic). The efficacy of antibacterial photodynamic treatments has been currently determined by using either viable colony counts (VCC) or metabolic assays (Alamar Blue) that were demonstrated to have critical limitations when used on microcolony-forming bacteria such as Streptococcus mutans. Materials and methods: Resin composite specimens were fabricated, wet-polished, ultraviolet-sterilized, and stored in water (72h). S. mutans (strain JM10) biofilms were grown [24h; 0.65xTHY with 0.1% (w/v) sucrose] on the surfaces of sterile specimens. Antibacterial treatments were performed by using MB (0.0005% and 0.001%) with or without LI (660 +/- 10nm, 6J/cm(2)). Specimens treated with chlorhexidine gluconate served as the negative control group. The efficacy of aPDT treatments was determined in terms of BL for intact biofilms and VCC for sonicated bacteria. Results: BL results were corrected by using the Greenhouse-Geisser method and were analyzed with repeated-measures analysis of variance and post hoc Bonferroni test (=0.05). VCC results were analyzed by using Kruskal-Wallis and Dunn's multiple-comparisons post hoc tests (=0.05). Our findings demonstrated that experimental treatments significantly decreased the viability of S. mutans biofilms (p<0.05). Moderate reductions in cellular viability were observed on biofilms subjected to aPDT treatments. Conclusions: This study demonstrated that aPDT has promising potential to be used as an additional method to control oral cariogenic biofilms.
Keywords: photochemotherapy; antibacterial agents; Streptococcus mutans; biofilms; decontamination; firefly luciferin; colony count; microbial